PRARANCANGAN PABRIK ASAM TEREFTALAT DARI PARAXYLENE DAN UDARA KAPASITAS 300.000 TON/TAHUN - , MUHAMMAD SILVANO IBRAHIM AIWAN; , Prof. Ir. Suryo Purwono, MA., Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Preliminary design of Terephtalic Acid Plant from Paraxylene and Air with production capacity of 300,000 ton/year is intended to fulfill terephtalic acid demands, hopefully also fulfill demands from foreign country. In order to fulfill the demands, 192.626,28 ton/year of paraxylene , 19.761,98 ton/year of acetic acid, and 1926,27 ton/year of cobalt (II) acetic are needed. . The main components react in 3 parallel CSTR reactors which operated isothermally in 2000C and the pressure is 20 atm. Because of very exothermic reaction to maintain the temperature in the reactor, there is coil cooling system. Utility needed to extend the process system consist of.4.854.581 ton/year demineralized water, 3446kW/year of electricity, 6.826.127,04 US gal/year of industrial fuel, dan 272.544,07 ton/year of saturated steam. The plant will be established in Kawasan Industri Cilacap (KCI) because the location near to PERTAMINA RU IV Cilacap that provide paraxylenes. Beside of that, the location of the plant also near to market targets which are Dimethyl Terephtalat and Pure Terephtalic Acid company that spreaded especially in Java. The area of the plant is 180.000m2 and 228 of manpower are needed. Fixed capital needed is Rp 353,169,858,507,00 + $ 57,551,956 and working capital of Rp 35.079.489.855,00 + $ 95.780.247,00. Based on economic analysis, the Return On Investment before tax is 59,74% and after tax is 28,79%. Pay Out Time befora tax is 1,31 year and after tax is 2,58 year. Break Even Point is 45,52 %, Shut Down Point is 30,03 % and Discounted Cash Flow Rate Of Return is 30,70 %. Therefore, further research on Terephtalic Acid Plant from Paraxylene and Air with production capacity of 300.000 ton/year should be carried out.